2013
DOI: 10.1155/2013/385473
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Flavonoids and Chlorogenic Acid in the Leaves ofArbutus unedoL. Using Thin Layer Chromatography

Abstract: The plant species Arbutus unedo shows numerous beneficial pharmacological effects (antiseptic, antidiabetic, antidiarrheal, astringent, depurative, antioxidant, antihypertensive, antithrombotic, and anti-inflammatory). For the medicinal use, standardization of extracts is a necessity, as different compounds are responsible for different biological activities. In this paper, we analyze monthly changes in the content of quercitrin, isoquercitrin, hyperoside, and chlorogenic acid. Methanolic extracts of the leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
(9 reference statements)
1
18
0
Order By: Relevance
“…In the cinnamic group of phenolics, chlorogenic acid was the major phenolic acid. However, chlorogenic acid had previously been reported only in the leaves of the strawberry tree, but not in its fruit (Maleš et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
“…In the cinnamic group of phenolics, chlorogenic acid was the major phenolic acid. However, chlorogenic acid had previously been reported only in the leaves of the strawberry tree, but not in its fruit (Maleš et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
“…The plate was put into the jar that contains mobile phase composed of toluene:ethyl acetate:methanol (5:3:2). The plate was put at the borderline and was observed by UV lamp at the wavelength 254 nm, and the Rf values were then measured (Males et al, 2013;Preethi et al, 2017;Rao & Ahmed, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Arbutin was reported as being present in leaf extracts of A. unedo collected in Montenegro, along with hydroquinone derivatives [46]. Quercitrin, isoquercitrin, hyperoside, and chlorogenic acid are other phenolic compounds identified and quantified by [5,47] in extracts of leaves of A. unedo from Croatia. In this work, the authors also reported that the concentrations of these compounds changed over the year.…”
Section: Chemical Composition Of a Unedomentioning
confidence: 99%